2020
DOI: 10.2147/ott.s257991
|View full text |Cite
|
Sign up to set email alerts
|

<p>Molecular Analysis of Oncogenic Mutations in Resected Margins by Next-Generation Sequencing Predicts Relapse in Non-Small Cell Lung Cancer Patients</p>

Abstract: Objective: To investigate the genetic mutations in both tumor and marginal tissues in patients with non-small cell lung cancer (NSCLC), and to evaluate the potential prognostic value in patients with margins gene positive. Methods: Next-generation sequencing (NGS) technique was used to detect genetic mutation in tumor and marginal tissues of the bronchus in 88 patients with NSCLC. Correlation of genetic mutations with pathology, lymph node metastasis, disease-free survival and overall survival was analyzed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[ 47 ] found that nearly 53% of the pancreatic cancer patients had detectable KRAS mutations in their H&E‐negative surgical margins samples, and these pancreatic cancer patients who were positive for surgical margins by the PCR‐based approach had a worse prognosis. Several gene mutations and DNA promoter hypermethylation changes were also successfully found in the surgical margins of NSCLC [ 48 , 49 ]. However, these studies had limited cohort size, utilized single gene sequencing data, or mainly focused on stage I‐II patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] found that nearly 53% of the pancreatic cancer patients had detectable KRAS mutations in their H&E‐negative surgical margins samples, and these pancreatic cancer patients who were positive for surgical margins by the PCR‐based approach had a worse prognosis. Several gene mutations and DNA promoter hypermethylation changes were also successfully found in the surgical margins of NSCLC [ 48 , 49 ]. However, these studies had limited cohort size, utilized single gene sequencing data, or mainly focused on stage I‐II patients.…”
Section: Discussionmentioning
confidence: 99%
“…The omics methodologies have been applied to a broad range of diseases. As some examples, survival in lung adenocarcinoma can be predicted by methylation signature [ 23 ], survival in patients with cancer of unknown primary can be improved with the use of whole-genome sequencing for therapy selection [ 24 ], and relapse in non-small lung cell cancer can be predicted by analyses of oncogenic mutations [ 25 ]. Via the combination of the different omics analyses, multi-omics analyses were established, making it possible to measure the different levels (e.g., mutational (genomics) and/or DNA methylation (epigenomics)) at which a pathway is affected.…”
Section: Introductionmentioning
confidence: 99%